Dana Desa: Apakah Solusi Mengatasi Persoalan Keuangan Desa? - Hendri Koeswara (Laboratorium Administrasi Publik FISIP Universitas Andalas, 2019)
Government Regulation No. 60 of 2014 on Village Fund sourced from the State Budget that is the commitment of the current government to build Indonesia from the periphery to strengthen the regions and villages. But it is not easy in terms of implementation, which qualified regulations, the ability and readiness of the village administration has not been up to make the Village Fund as a dilemma in dealing with financial issues the village to the regression or independence in the village itself in financial terms. The purpose of this research that using a qualitative approach is to approach the budget cycle theory according to Mullins is as follows; (1) To describe the implementation of the program of the Village Fund in Fiscal Year 2015 (2) To determine the progress in implementation of the Village Fund in Fiscal Year 2015 (3) To determine the readiness of regional government regulations and the document is the village planning in the implementation of the Village Fund, (4) To determine the impact of the Village Fund in overcoming the financial problems the village, (5) To know the considerations made by the village government in determining spending priorities aspect penggunanaan village of Village Fund, and (6) To determine the best model of financial planning villages in rural development. The results obtained are the Village Fund is a solution in overcoming the financial constraints the current village. However, there are still shortcomings in optimizing the utilization of the Village Funds, such as the lack of regulations that should be issued by the district / city governments and the late planning documents, the conflicting priority policies of village use that are sometimes different from the needs of the village community, so the choice and pragmatic way becomes dominant. So,it still needs an effective village’s planning model in the optimization of the various sources of income to the next village.